Political activities of Sophronius Vrachanski - Rusin, Bartłomiej (Balcanica Posnaniensia. Acta et studia, 2024)
The beginning of the 19th century was a difficult period for the Bulgarian population, caused by a deep crisis in the Ottoman Empire and another Russo–Turkish war of 1806–1812. During the conflict, the former bishop of Vratsa, Sophronius, together with a circle of activists, undertook political action to support the Russian military effort and help the civilian population fleeing the horrors of the war. This action ultimately ended in failure, as it was not possible to obtain autonomy for the Bulgarians, but the political program they developed was an important stage in the formation of the native national liberation movement. Thanks to his achievements, Sophroniy is known in Bulgarian historiography not only as a priest and one of the codifiers of the modern Bulgarian language, but also as a political activist.